A Proteomic Characterization of Bordetella pertussis Clinical Isolates Associated with a California State Pertussis Outbreak. (24th May 2015) - Williamson, Yulanda M.; Moura, Hercules; Whitmon, Jennifer; Woolfitt, Adrian R.; Schieltz, David M.; Rees, Jon C.; Guo, Stephanie; Kirkham, Heather; Bouck, Daniel; Ades, Edwin W.; Tondella, Maria Lucia; Carlone, George M.; et al.
Abstract : Bordetella pertussis ( Bp ) is the etiologic agent of pertussis (whooping cough), a highly communicable infection. Although pertussis is vaccine preventable, in recent years there has been increased incidence, despite high vaccine coverage. Possible reasons for the rise in cases include the following: Bp strain adaptation, waning vaccine immunity, increased surveillance, and improved clinical diagnostics. A pertussis outbreak impacted California (USA) in 2010; children and preadolescents were the most affected but the burden of disease fell mainly on infants. To identify protein biomarkers associated with this pertussis outbreak, we report a whole cellular protein characterization of six Bp isolates plus the pertussis acellular vaccine strain Bp Tohama I (T), utilizing gel-free proteomics-based mass spectrometry (MS). MS/MS tryptic peptide detection and protein database searching combined with western blot analysis revealed three Bp isolates in this study had markedly reduced detection of pertactin (Prn), a subunit of pertussis acellular vaccines. Additionally, antibody affinity capture technologies were implemented using anti- Bp T rabbit polyclonal antisera and whole cellular proteins to identify putative immunogens. Proteome profiling could shed light on pathogenesis and potentially lay the foundation for reduced infection transmission strategies and improved clinical diagnostics.